Binational reflections on pathways to groundwater security in the Mexico–United States borderlands. Issue 7 (17th November 2021) - Sanchez, Rosario; Breña-Naranjo, José Agustin; Rivera, Alfonso; Hanson, Randall T.; Hernández-Espriú, Antonio; Hogeboom, Rick J.; Milman, Anita; Benavides, Jude A.; Pedrozo-Acuña, Adrian; Soriano-Monzalvo, Julio Cesar; Megdal, Sharon B.; Eckstein, Gabriel; et al.
ABSTRACT: Shared groundwater resources between Mexico and the United States are facing unprecedented stressors. We reflect on how to improve water security for groundwater systems in the border region. Our reflection begins with the state of groundwater knowledge, and the challenges groundwater resources face from a physical, societal and institutional perspective. We conclude that the extent of ongoing cooperation frameworks, joint and remaining research efforts, from which alternative strategies can emerge, still need to be developed. The way forward offers a variety of cooperation models as the future offers rather complex, shared and multidisciplinary water challenges to the Mexico–US borderlands.